The Role of Actuarial Profile, Corporate Governance, and Actuarial Backup on Price to Book Value: A Study on Public Insurance Company in Indonesia - Ika Dewi Nurida; Moch. Doddy Ariefianto (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study investigates the role of the actuarial Profile, corporate governance, and actuarial reserves in influencing the company's book value. We apply panel data econometric to a dataset comprising ten companies, annual frequency from 2006 to 2019; 140 yearly company observations. We find that size positively affects the price to book value. On the other hand, actuarial Profile and corporate governance (institutional ownership) negatively correlate with the price to book value. This study brings important implications to business/regulatory practices for Financial Services Authority regulators. This study is expected to be able to provide a reference for future research related to the insurance industry.